Diagnosis of pathogens causing bacterial meningitis using Nanopore sequencing in a resource-limited setting - Pallerla, Srinivas Reddy; Van Dong, Do; Linh, Le Thi Kieu; Van Son, Trinh; Quyen, Dao Thanh; Hoan, Phan Quoc; Trung, Ngo Tat; The, Nguyen Trong; Rüter, Jule; Boutin, Sébastien; Nurjadi, Dennis; Sy, Bui Tien; et al. (Annals of clinical microbiology and antimicrobials, 2022)
The aim of the present study is to compare the performance of 16S rRNA Nanopore sequencing and conventional culture in detecting infectious pathogens in patients with suspected meningitis in a resource-limited setting without extensive bioinformatics expertise.
Gesehen am 27.10.2022